Right Ventricular Myocardial Infarction Complicated by Cardiac Arrest: Utilization of Extracorporeal Membrane Oxygenation - Alisha Alabre-Bonsu; Saurav Uppal; Ernest L. Mazzaferri; Konstantinos Dean Boudoulas (Case Reports in Cardiology)
A 44-year-old male with an out-of-hospital cardiac arrest due to an acute left ventricular (LV) inferoposterior wall myocardial infarction (MI) involving the right ventricle (RV) is presented. This case highlights the challenges in the management of patients with cardiac arrest, indications for use of ventricular assist devices, potential effects of LV assist devices on the RV in the setting of RV MI, and culprit versus complete coronary artery revascularization in these patients.